Clinico-radiologic discordance: A case of superior semicircular canal dehiscence by superior petrosal sinus: Superior semicircular canal dehiscence by superior petrosal sinus - Bülbül, Erdoğan; Canakcı , Hasan; Yanık , Bahar; Yazıcı , Hasmet; Akay , Emrah (Journal of Surgery and Medicine, 2024)
The audio-vestibular symptoms caused by the partial absence of the bony structure surrounding the superior semicircular canal (SCC) are known as superior canal dehiscence syndrome (SCDS). The dehiscence region can be seen in high-resolution computed tomography (HRCT). Dehiscence is often seen at the arcuate eminence level in the apical region of the SCC. The superior petrosal sinus may rarely course in the vicinity of the medial wall of the SCC and can even cause SCDS. The vascular origin of the dehiscence cannot be exactly determined in routine HRCT without contrast agent administration. In the literature, the use of contrast-enhanced magnetic resonance imaging (MRI) has been reported in a small number of cases to demonstrate this pathology. There may be a relationship between the degree of dehiscence demonstrated by MRI and the patient's symptoms. Here, we present a case that is thought to be superior petrosal sinus dehiscence to SCC using HRCT. Contrast-enhanced arterial and venous phase 3D T1-weighted MRI was performed for the confirmation of the diagnosis, but there was no good correlation between the degree of radiological dehiscence and symptoms in contrast to the previous literature.